2013
DOI: 10.1371/journal.pone.0077873
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Household Transmission of Pandemic (H1N1) 2009 among Self-Quarantined Patients in Beijing, China

Abstract: As the pandemic (H1N1) 2009 progressed, the Ministry of Health of China advised cases with mild symptoms to remain home for isolation and observation, which may have increased the risk for infection among other household members. Describing the transmission characteristics of this novel virus is indispensable to effectively controlling the spread of disease; thus, the aim of this study was to assess risk factors associated with household transmission of pandemic H1N1 from self-quarantined patients in Beijing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…The inverse relationship between the size of households and the probability of being influenza cases listed in Table 1 was also observed in several studies [24,[37][38][39]. Although the trends of proportion of influenza cases by household size vary from study to study, possible factors such as the proportion of child [24], contact pattern, hygiene behaviour, ventilation status [40], and difference in social network pattern [39] implying the heterogeneity across households may contribute to the observed pattern.…”
Section: Discussionsupporting
confidence: 62%
“…The inverse relationship between the size of households and the probability of being influenza cases listed in Table 1 was also observed in several studies [24,[37][38][39]. Although the trends of proportion of influenza cases by household size vary from study to study, possible factors such as the proportion of child [24], contact pattern, hygiene behaviour, ventilation status [40], and difference in social network pattern [39] implying the heterogeneity across households may contribute to the observed pattern.…”
Section: Discussionsupporting
confidence: 62%
“…Our mechanistic model suggests that an average of 5% reduction in transmission likelihood could result in the ILI dynamics observed of the 2019-2020 season. Past studies have shown that frequent, e↵ective handwashing can result in a comparable moderate reduction in infections [23,24,25]. A meta-analysis of the e↵ects of NPIs in reducing influenza transmission demonstrated that hand hygiene was significant in reducing influenza transmission, with an odds ratio of 0.62 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Intense contact between same age groups and between children and parents has been documented in studies of social mixing patterns [ 4 , 29 ]. These data suggest that household transmission can be prevented by decreasing the contact intensity through measures such as home quarantine [ 30 ]. In addition, longer school absence duration was associated with longer SIs.…”
Section: Discussionmentioning
confidence: 99%